Recent advances in immunoassay technologies for the detection of human coronavirus infections - Wang, Danqi; Chen, Yuejun; Xiang, Shan; Hu, Huiting; Zhan, Yujuan; Yu, Ying; Zhang, Jingwen; Wu, Pian; Liu, Fei yue; Kai, Tianhan; Ding, Ping (Frontiers in Cellular and Infection Microbiology, 2023)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is the seventh coronavirus (CoV) that has spread in humans to date and has become a global pandemic since late 2019. Efficient and accurate laboratory diagnostic methods are one of the crucial means to control the development of the current pandemic and prevent potential future outbreaks. Although real-time reverse transcription-polymerase chain reaction (rRT-PCR) is the preferred laboratory method recommended by the World Health Organization (WHO) for the diagnosis and screening of SARS-CoV-2 infection and has been widely used, the versatile serological testing methods still play an important role in the work of pandemic control. They can be used not only as supplementary tools to identify cases missed by rRT-PCR, but also for first-line screening tests in areas with limited medical resources. Moreover, they are also indispensable tools for retrospective epidemiological surveys and the evaluation of the effectiveness of vaccination. In this review, we, firstly, summarize the mainstream serological testing methods for the human coronaviruses (HCoVs), discuss their technical characteristics, benefits, limitations, and application scopes. The technical strategies were proposed based on bioinformatics and biosensors to improve the performance of these methods. Finally, future suggestions and possibilities that can lead to higher sensitivity and specificity are provided for further research.